Erratum to: Root and leaf anatomy of some terrestrial representatives of the Cranichideae tribe (Orchidaceae) - de Cássia Andreota, Rita [UNESP] (2015)
Departamento de Botânica, Instituto de Biociências, Universidade Estadual Paulista – UNESP, Avenida, 24 A, 1515, Bela Vista